2003
DOI: 10.1021/jo030131t
|View full text |Cite
|
Sign up to set email alerts
|

Spiro-Fused (C2)-Azirino-(C4)-pyrazolones, a New Heterocyclic System. Synthesis, Spectroscopic Studies and X-ray Structure Analysis1

Abstract: Reaction of 1-substituted 4-acyl-5-hydroxy-3-methyl-1H-pyrazoles (2) with hydroxylamine gives the corresponding "oximes" 3, which are mainly present as (Z)-2,4-dihydro-4-[(hydroxyamino)methylene]-3H-pyrazol-3-ones. Treatment of compounds 3 with trichloroacetyl isocyanate/potassium carbonate in anhydrous diethyl ether affords 7-methyl-1,5,6-triazaspiro[2.4]hepta-1,6-dien-4-ones (4). The structure of compounds 4 was elucidated by means of single-crystal X-ray analysis (4f, 4h) and confirmed by NMR spectroscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In the course of a program devoted to the synthesis of new heterocyclic scaffolds for bioactive compounds,1–10 we recently presented the synthesis of various [5,6]pyrano[2,3‐ c ]pyrazol‐4(1 H )‐ones of type 4 via reaction of 2‐pyrazolin‐5‐ones 1 with o ‐haloheteroarenecarbonyl chlorides 2 and the subsequent ring closure of the resulting 4‐heteroaroylpyrazol‐5‐ols 3 (Scheme ). Following this approach, we have obtained type 4 compounds carrying—among others—a pyridine (all positional isomers),1 quinoline,1 thiophene (all positional isomers),2, 3 benzo[b]thiophene,2 and thieno[2,3‐ b ]thiophene system3 as the variable heteroaromatic moiety (‘Het’) condensed to the central γ‐pyranone ring.…”
Section: Introductionmentioning
confidence: 99%
“…In the course of a program devoted to the synthesis of new heterocyclic scaffolds for bioactive compounds,1–10 we recently presented the synthesis of various [5,6]pyrano[2,3‐ c ]pyrazol‐4(1 H )‐ones of type 4 via reaction of 2‐pyrazolin‐5‐ones 1 with o ‐haloheteroarenecarbonyl chlorides 2 and the subsequent ring closure of the resulting 4‐heteroaroylpyrazol‐5‐ols 3 (Scheme ). Following this approach, we have obtained type 4 compounds carrying—among others—a pyridine (all positional isomers),1 quinoline,1 thiophene (all positional isomers),2, 3 benzo[b]thiophene,2 and thieno[2,3‐ b ]thiophene system3 as the variable heteroaromatic moiety (‘Het’) condensed to the central γ‐pyranone ring.…”
Section: Introductionmentioning
confidence: 99%
“…The major product was identified to be the 5-hydroxy-4-acylpyrazole derivative 5a, which can be present in several tautomeric forms, hampering its NMR spectroscopic characterization. 15 When we repeated the reaction using a series of hydrazones 2 ( Table 1) we observed that in most of the cases large amounts of 5 are obtained. In some cases as with the N-Boc-N-methylhydrazones 2c, 2d, and 2f (Table 1) the reaction afforded only the corresponding hydroxypyrazole 5, with no trace of the desired ketoimine 4.…”
Section: Resultsmentioning
confidence: 92%
“…Several methods have been established for the Neber rearrangement by using bases like K 2 CO 3 [28,29] and Na 2 CO 3 [30–32]. Holzer and his group established a Neber rearrangement using K 2 CO 3 that tolerates an oxime activating group O ‐(trichloroacetate), which has been used in the preparation of spirocyclic 2 H ‐azirines (Scheme 15) [28].…”
Section: Neber Rearrangementmentioning
confidence: 99%